2018
DOI: 10.12659/msm.906910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moisture Content and Loading Profile on Changing Properties of Bone Micro-Biomechanical Characteristics

Abstract: BackgroundOur study explored the influences of hydration conditions and loading methods on the mechanical properties of cortical bones and cancellous bones.Material/MethodsElastic modulus and hardness of human cortical bones and cancellous bones that contained different moisture levels (20%, 30%, 40%, 50%, and 60%) were measured with nanoindentation with different peak loads and loading rates. Cortical bones with 20% and 60% moisture were tested with 30 nm, 40 nm, and 50 nm peak loads at 6 nm/s, 8 nm/s, and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…15a), it was established that the hardness of the undrained bone tissue specimen was 55 MPa, while the hardness of the fluid-saturated bone was 47 MPa, and the elastic moduli were 3.9 and 3.6 GPa, respectively. The results obtained correspond qualitatively to the data on the influence of fluid on the mechanical response of bone tissue by other authors [72][73][74].…”
Section: Validation Of the Materials Modelsupporting
confidence: 90%
“…15a), it was established that the hardness of the undrained bone tissue specimen was 55 MPa, while the hardness of the fluid-saturated bone was 47 MPa, and the elastic moduli were 3.9 and 3.6 GPa, respectively. The results obtained correspond qualitatively to the data on the influence of fluid on the mechanical response of bone tissue by other authors [72][73][74].…”
Section: Validation Of the Materials Modelsupporting
confidence: 90%
“…The mechanical properties were expected to be affected by the hydration state, as dried bone is expected to become stiffer and more brittle (Smith and Walmsley, 1959;Broz et al, 1993;Conrad et al, 1993;Nyman et al, 2006;Lievers et al, 2010;Granke et al, 2015;Lin, 2016;Wang et al, 2018). Conrad et al (1993) assessed changes in mechanical behavior of trabecular bone due to freezedrying and found that freeze-drying followed by rehydration for 24 h caused a 24% increase in stiffness compared to freshly frozen controls and that non-rehydrated freeze-dried specimens were 33% stiffer than rehydrated specimens (Conrad et al, 1993).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The mechanical properties of bone are dependent on the hydration state of the tissue and drying alters the mechanical behavior in terms of increased stiffness and brittleness on the nano-, meso-and macro-scales (Smith and Walmsley, 1959;Broz et al, 1993;Conrad et al, 1993;Nyman et al, 2006;Lievers et al, 2010;Granke et al, 2015;Lin, 2016;Wang et al, 2018). Hence, for physiologically relevant assessment of the mechanical properties, the specimen should be hydrated when tested mechanically.…”
Section: Introductionmentioning
confidence: 99%